One-pot, Four-Component Green Synthesis, Carbonic Anhydrase II Inhibition and Docking Studies of 5-Arylidenerhodanines - KULABAŞ, NECLA (WILEY-V C H VERLAG GMBH, 2018)
In the present study, a planning strategy for N-substituted-5-arylidenerhodanines was developed by the condensation between 3-morpholinopropan-1-amine, aldehyde, ethyl bromoacetate and carbon disulfide in the presence of trimethylamine in water via a one-pot, sequential four component reaction at room temperature and additionally microwave and ultrasound irradiated techniques. The synthesis of arylidenerhodanine derivatives was performed through the optimized one pot strategy starting from commercially available materials in high yields and purity without troublesome work-ups, after recrystallization from an appropriate solvent. Enzyme inhibition activity screening studies on CA II was also carried out. IC50 values of some of examined molecules could be determined and it was observed that they were nanomolar level except for 1r, and lower than that of reference molecule. The inhibition in the range of 8.6-99.4% was seen in the presence of newly synthesized molecules at their reachable maximum concentration in the reaction mixtures. Among the examined molecules, 5a and 5p with the two lowest IC50 values were found to be the most potent inhibitors. In silico studies showed that all of the rhodanine derivatives have higher affinity than reference ligand against binding site, while none of the compounds have demonstrated any interaction with Zn2+ as with the classical sulfonamides.
Keywords: Rhodanine; sulfonamide carbonic anhydrase II; inhibition; docking; microwave irradiaton; ultrasound sonication; MICROWAVE-ASSISTED SYNTHESIS; BIOLOGICAL EVALUATION; RHODANINE DERIVATIVES; ANTICANCER ACTIVITY; HYBRID MOLECULES; IX; EFFICIENT; BEARING; DISCOVERY; XII